Molecular Detection of Virulence Genes of E. coli in Urinary Tract Infections in Dogs - Sandeep Siwach; Ruchi Tiwari; Ajay Pratap Singh; Rashmi Singh; Ambika Arun; Ranjana Singh; Meenakshi Singh (The Indian Veterinary Journal, 2026)
Urinary tract infections (UTIs) are the most common bacterial infections in dogs, with E. coli being the predominant etiological agent. In this study, 18 E. coli isolates obtained from canine UTI cases were investigated for the presence of selected virulence-associated genes and their antimicrobial resistance profile. Standard bacteriological methods confirmed the isolates, and polymerase chain reaction (PCR) was used to detect the fimH, hlyA, and papC virulence genes. Antibiotic susceptibility test was used using the disc diffusion method. Molecular analysis revealed the presence of fimH in the majority of isolates; papC and hlyA were detected in a few isolates, indicating varying virulence potentials among the strains. Antibiogram profiling indicated a high level of resistance to β-lactam antibiotics, cephalosporins, and aminoglycosides, highlighting the emergence of multidrug-resistant E. coli in canine UTIs. The findings emphasized the role of virulence genes in the pathogenesis of canine UTIs and underlined the need for routine molecular surveillance and judicious antimicrobial use in veterinary care.